Calculation of Steel Reinforcement Needs for Beams and Prestressed Beams: Case Study on a Residential Project in South Jakarta - Rifaldi Adi Saputra; Agung Sakti Meldian; Riris Setiyowati; Arman Jayadi (Jurnal Teknik dan Science, 2025)
This study aims to analyze the need for reinforcement in conventional and prestressed beams in a residential project in South Jakarta. A quantitative descriptive approach is used, allowing for the systematic and measurable presentation of numerical data. Data were collected through direct field surveys, focusing on the analysis of work execution methods and the calculation of steel reinforcement requirements, particularly for ground floor structural elements. The case study was conducted on a conventional beam of type As 4' ; E - I with a span of 22.40 meters, which resulted in an iron demand volume of 991.77 kg for 25 mm diameter and 472.37 kg for 13 mm diameter. Meanwhile, for the prestressed beam As J; 3 - 8 with a cross-sectional size of 400 x 500 mm and a span of 14.30 meters, an iron requirement of 526.96 kg for a diameter of 22 mm and 295.00 kg for a diameter of 13 mm was obtained. The results of this study provide a detailed estimation of the material requirements for reinforcing the residential structure, which can serve as a reference for planning and controlling construction costs.